Odpowiedzi

2010-03-09T16:16:46+01:00
A) 0=3-(2x+1)
0=3-2x-1
0-3+1=-2x
-2=-2x
-2x=-2
x=1
2010-03-09T16:18:40+01:00
A) 0= 3-(2x+1)
0=3-2x-1
2x=2
x=1
b) 0=(x-1)-(3x-5)
0= x-1-3x+5
0= -2x+4
2x= 4
x= 2
c)(¹₂x+1) +³₂x=3
1/2x+1+3/2x=3
2x=2
x=1
d) 3(1-x) - (1-2x)=9
3-3x-1+2x=9
-x=5
x=-5
e) 0,5 (s-4x)=3-x
1/2s-2x=3-x

Najlepsza Odpowiedź!
2010-03-09T16:19:14+01:00
A) 0= 3-(2x+1)
0= 3 - 2x - 1
2x = 2 /:2
x = 1

b) 0=(x-1) - (3x-5)
0 = x - 1 - 3x + 5
0 = -2x + 4
2x = 4 /:2
x = 2

c)(¹/₂x+1) +³/₂x=3
0,5x + 1 + 1,5x = 3
2x = 3- 1
2x = 2 /:2
x = 1

d) 3(1-x) - (1-2x)=9
3 - 3x - 1 + 2x = 9
3 - 3x - 1 + 2x = 9
-x = 5
x = -5

e) 0,5 (s-4x)=3-x
0,5 - 2x = 3 - x
-x = 3 + 0,5
-x = 3,5 /:(-1)
x = -3,5

e) 2 możliwość

0,5 (s-4x)=3-x
1/2s - 2x = 3 - x
1/2s - x = 3 /x2
s - 2x = 6